THE CORRELATION OF SMARTPHONE OVERUSE, PSYCHOLOGICAL PROBLEMS, AND SLEEP STATUS IN NURSING STUDENTS - Ferdy Lainsamputty; Metty Wuisang (Nursing Sciences Journal, 2025)
Nursing students tend to overuse smartphones, and when this is combined with psychological issues, it often disrupts their sleep patterns. This study aimed to investigate the correlation of smartphone overuse, psychological problems, sleep quality, and daytime sleepiness among professional nursing students. Descriptive correlational and cross sectional design were employed. The samples were recruited using convenience sampling technique involving 110 students. The questionnaires were Smartphone Addiction Scale-Short Version (SAS-SV), Depression, Anxiety Stress Scale-42 (DASS-42), Pittsburgh Sleep Quality Index (PSQI), and Epworth Sleepiness Scale (ESS).  Pearson correlation was utilized to examine the correlation between study variables. Majority of students were addicted to smartphone (65.5%), poor sleepers (78.2%), and had excessive daytime sleepiness (EDS) (54.5%). Sleep quality was negatively correlated to depression (r=-0.335, p<0.001), anxiety (r=-0.333, p<0.001), and stress (r=0.331, p<0.001). EDS had correlation with smartphone overuse (r=0.315, p=0.001), depression (r=0.252, p=0.008), anxiety (r=0.288, p=0.002), dan stress (r=0.216, p=0.024). Participants with poorer psychological problrmes were trying to manage their sleep quality to be better, even though still experienced EDS. Future studies could investigate the factors contributing to excessive smartphone use, psychological influences, and other elements impacting sleep, while also incorporating more objective methods to improve data precision.